Community Support for Money Politics in the Simultaneous Village Head Election - Setiadi, Ozi (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2024)
This research aims to discuss community support for money politics in the simultaneous village head election. Community support for money politics in village head elections is still found. Society accepts, even supports money politics and considers this to be normal. This research is field research with a qualitative approach. Data was obtained through indirect observation, focus group discussions (FGD), and unstructured interviews. Interviews were conducted with religious leaders, community leaders, village head candidates and village heads. The data analysis stages were carried out using interpretation analysis techniques. As a result, public support for money politics results in changes in people's behavior who tend not to be active in development. Because society has a transactional mindset, so the election of village heads is carried out on the basis of economic transactions alone. Money politics occurs as a result of weak political education.